2019
DOI: 10.1007/s10461-019-02392-0
|View full text |Cite
|
Sign up to set email alerts
|

Recalling, Sharing and Participating in a Social Media Intervention Promoting HIV Testing: A Longitudinal Analysis of HIV Testing Among MSM in China

Abstract: Social media interventions may enhance HIV services among key populations, including men who have sex with men (MSM). This longitudinal analysis examined the effect of recalling, sharing, and participating in different components of a social media intervention on HIV testing among MSM. The social media intervention included six images/texts and information about an online local community contest to promote testing. Of the 1033 men, they recalled a mean of 2.7 out of six images and shared an average of one imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Considering the aforementioned issue, social media intervention has been used to promote social support and strengthen community connection among MSM [48, 49]. A longitudinal study suggests that social media interventions can enhance HIV services among MSM in China, with participating online local community contests to promote HIV testing [50]. In 2010, Chongqing CDC and relevant NGOs committed to construct network platforms by utilising WeChat and websites to spread knowledge and skills about HIV/AIDS prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the aforementioned issue, social media intervention has been used to promote social support and strengthen community connection among MSM [48, 49]. A longitudinal study suggests that social media interventions can enhance HIV services among MSM in China, with participating online local community contests to promote HIV testing [50]. In 2010, Chongqing CDC and relevant NGOs committed to construct network platforms by utilising WeChat and websites to spread knowledge and skills about HIV/AIDS prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Digital approaches can reach remote participants, limit stigma, provide a platform for anonymity and privacy, and increase community engagement [7,[9][10][11]. Previous surveys suggested that digital interventions can promote HIV testing and safe sexual behaviors through providing information related to HIV, offering HIV testing services, collecting different creative ideas to design intervention and linking people to the community [10,12]. In China, the Internet has become a major way to find gay partners among MSM [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Of 18 manuscripts included in this review, 15 reported results of feasibility studies ( Alarcón Gutiérrez et al, 2018 ; Anand et al, 2015 ; Elliot et al, 2016 ; Horvath et al, 2013 ; Huang et al, 2017 ; Lampkin et al, 2016 ; Lelutiu-Weinberger et al, 2015 ; Patel et al, 2020 ; Pedrana et al, 2013 ; Sun et al, 2015 ; Tanner et al, 2018 ; Vogel et al, 2019a ; Washington et al, 2017 ; Young and Jaganath, 2013 ; Zhu et al, 2019 ). Three studies reported results of either efficacy ( Bull et al, 2012 ) or effectiveness trials ( Cao et al, 2019 ; Vogel et al, 2019b ). Characteristics of each study are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%